2005
DOI: 10.1002/jez.a.235
|View full text |Cite
|
Sign up to set email alerts
|

Development of gene transfer technology for black tiger shrimp,Penaeus monodon

Abstract: An effective foreign gene transfer method for shrimp would have several potential uses in the shrimp culture industry, such as in preventing infectious diseases. We evaluated two gene transfer methods and used black tiger shrimp, Penaeus monodon, as a model target species. For a promoter, we used the 1,592-bp promoter region of the EF-1alpha gene, a house-keeping gene, of kuruma shrimp Marsupenaeus japonicus. The promoter region was linked to either the gene for green fluorescence protein (GFP) or the gene for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
17
1
2
Order By: Relevance
“…This differs from the results obtained in Macrobrachium rosenbergii (Li and Tsai 2000). Other reports have demonstrated that CMV, as well as SV40, RSV, MT-1 and carp b-actin promoters, are functional in penaeid shrimp (Bensheng and Khoo 1997;Tseng et al 2000;Arenal et al 2000Arenal et al , 2004Sun et al 2005;Yazawa et al 2005). There were no significant differences on the survival rate among the groups.…”
Section: Discussioncontrasting
confidence: 61%
“…This differs from the results obtained in Macrobrachium rosenbergii (Li and Tsai 2000). Other reports have demonstrated that CMV, as well as SV40, RSV, MT-1 and carp b-actin promoters, are functional in penaeid shrimp (Bensheng and Khoo 1997;Tseng et al 2000;Arenal et al 2000Arenal et al , 2004Sun et al 2005;Yazawa et al 2005). There were no significant differences on the survival rate among the groups.…”
Section: Discussioncontrasting
confidence: 61%
“…To directly test the function of developmental genes, microinjection of transgenes or interfering RNAs will need to be performed on eggs, which is technically challenging. Microinjection of plasmid DNA has been reported for Penaeus japonicus (Preston et al 2000 ), P. monodon (Yazawa et al 2005 ), and P. vannamei (Sun et al 2005 ). In the amphipod crustacean Parhyale hawaiensis , microinjection of interfering RNAs into embryos demonstrated the necessity for vasa in germ line maintenance but not its initial formation (Özhan-Kizil et al 2009 ).…”
Section: Experimental Developmental Geneticsmentioning
confidence: 95%
“…In recent studies, promoters of the single whey acidic protein (WAP) domain-containing protein gene (Chen et al 2006b) and EF-1α gene (Yazawa et al 2005) isolated from marine shrimps have been demonstrated to drive protein expression comparable to CMVp. In addition to these, a WSSV promoter (Immediate early ie1 promoter) has also been tested in shrimps .…”
Section: Dna Vector-based Rnaimentioning
confidence: 99%
“…Cytomegalovirus promoter (CMVp) cannot be used for shRNA vectors as they append 5' vector sequences and 3' poly AA sequences, which inhibit shRNA function, but are ideal for lhRNA constructs. Apart from CMV immediate early promoter, other pol II promoters that are suitable for lhRNA expression and known to be active in shrimps include β-actin and SV40 early promoters (Arenal et al 2000).In recent studies, promoters of the single whey acidic protein (WAP) domain-containing protein gene (Chen et al 2006b) and EF-1α gene (Yazawa et al 2005) isolated from marine shrimps have been demonstrated to drive protein expression comparable to CMVp. In addition to these, a WSSV promoter (Immediate early ie1 promoter) has also been tested in shrimps .…”
mentioning
confidence: 99%